Extracellular vesicles and cancer stem cells: a deadly duo in tumor progression - Tayanloo-Beik, Akram; Eslami, Azin; Sarvari, Masoumeh; Jalaeikhoo, Hasan; Rajaeinejad, Mohsen; Nikandish, Mohsen; Faridfar, Ali; Rezaei-Tavirani, Mostafa; Mafi, Ahmad Rezazadeh; Larijani, Bagher; Arjmand, Babak (Oncology Reviews, 2024)
The global incidence of cancer is increasing, with estimates suggesting that there would be 26 million new cases and 17 million deaths each year by 2030. Cancer stem cells (CSCs) and extracellular vesicles (EVs) are key to the resilience and advancement of cancer. They play a crucial role in tumor dynamics and resistance to therapy. CSCs, initially discovered in acute myeloid leukemia, are well-known for their involvement in the beginning, advancement, and reappearance of tumors, mostly because of their distinct characteristics such as resistance to drugs and ability to self-renew. EVs, which include exosomes, microvesicles, and apoptotic bodies, play a vital role in facilitating communication between cells within the tumor microenvironment. They have a significant impact on cellular behaviors and contribute to genetic and epigenetic changes.This paper analyzes the mutually beneficial link between CSCs and EVs, emphasizing their role in promoting tumor spread and developing resistance mechanisms. The review aims to investigate the interaction between these entities in order to discover new approaches for attacking the complex machinery of cancer. It highlights the significance of CSCs and EVs as crucial targets in the advancement of novel cancer treatments. The purpose of the insights offered is to stimulate additional research, promoting progress in ideas for cancer treatment, and providing renewed optimism in the effort to reduce the burden of cancer.